Mahmoud, Houzan. Kurdish Women’s Stories. Londres, Pluto Press, 2021. ISBN: 978-17-86806482. 206 páginas - Guarche Ribeiro, María Florencia (Investigaciones Feministas, 2022)
Reseña del libro de Mahmoud, Houzan. Kurdish Women’s Stories. Londres, Pluto Press, 2021. ISBN: 978-17-86806482. 206 páginas